Educational Implications of Early Marriage and Family Counseling-Based Solutions - Kabata, Benyamin Ngongu (Civiliza Publishing, Indonesia., 2025)
Marriage is a physical and spiritual bond between a man and a woman who has an important role in community life, because marriage is a bond and procession that legitimizes the relationship between a man and a woman. This study aims to determine the impact of early marriage and its solutions from the perspective of Family Counseling Guidance, so that it can examine how early marriage can occur, who is involved in the problem and its consequences. The method in this study uses qualitative research using primary and secondary data sources through interviews, observations and documentation from Sopo Village, Amanuban Tengah District, South Timor Tengah Regency. Data collection using field research using qualitative and descriptive analysis methods. The results of the study show that early marriage has an impact on family harmony, especially between husband and wife. The positive impact is that they still have a very strong physical and mentality and have been blessed with children, so that they can educate children in completing their studies and even to a higher level. While the negative impact: the husband and wife have not thought carefully both physically and mentally. So that there is boredom in marriage, and economically also not able to finance household life.